1983
DOI: 10.1177/07399863830051007
|View full text |Cite
|
Sign up to set email alerts
|

A Prompt/Reward Technique to Elicit Socially Acceptable Behavior with Chicano Gang Delinquents

Abstract: This paper examines the effect of two types of prompts in eliciting a zero-or low-probability behavior in three Chicano gang members. The target behavior consisted of a chain of responses terminating in the publication of writing and art work in a community newsletter. A general prompt was ineffective, but subject-specific prompts elicited a total of 38 pages of work. The relevance of this study for behavior therapy with similar subjects is discussed. The advantages and special problems of research in the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Researchers have manipulated dimensions of prompting (i.e., specificity, frequency) to determine the most effective way to prompt. Hunsaker (1983) demonstrated that specific prompts were more effective than general prompts. That is, face-to-face conversations (specific) were more effective than a written flyer (general), when paired with reinforcement, at increasing pages written (i.e., work completion) by Hispanic youth with a history of juvenile delinquency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have manipulated dimensions of prompting (i.e., specificity, frequency) to determine the most effective way to prompt. Hunsaker (1983) demonstrated that specific prompts were more effective than general prompts. That is, face-to-face conversations (specific) were more effective than a written flyer (general), when paired with reinforcement, at increasing pages written (i.e., work completion) by Hispanic youth with a history of juvenile delinquency.…”
mentioning
confidence: 99%
“…In sum, researchers have demonstrated that prompting is an effective strategy for increasing appropriate, and decreasing inappropriate, behavior across a range of individuals (preschool students, individuals with disabilities, and adults) and settings (school and community). The most effective prompts are specific (Hunsaker, 1983) and frequent (Lancioni et al, 2001;Lombard et al, 1995), with the actual frequency determined by characteristics of the learner and desired behavior(s). Although prompts are typically delivered in the setting where behavior is expected, prompts may still be effective when delivered in a different setting and minutes (or more) before the behavior (Austin et al, 1998;Lombard et al, 1995).…”
mentioning
confidence: 99%